2003
DOI: 10.1242/jcs.00220
|View full text |Cite
|
Sign up to set email alerts
|

Calcium regulation of actin crosslinking is important for function of the actin cytoskeleton inDictyostelium

Abstract: The actin cytoskeleton is sensitive to changes in calcium, which affect contractility, actin-severing proteins, actin-crosslinking proteins and calmodulin-regulated enzymes. To dissect the role of calcium control on the activity of individual proteins from effects of calcium on other processes,calcium-insensitive forms of these proteins were prepared and introduced into living cells to replace a calcium-sensitive form of the same protein. Crosslinking and bundling of actin filaments by the Dictyostelium 34 kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…Therefore, it has been proposed that CTinduced model Hirano body formation may be the result of increased F-actin binding and loss of calcium regulation (16). Further studies using additional mutated forms of the 34-kDa protein are consistent with the conclusion that activation of actin binding and loss of calcium regulation are biochemical properties invariably associated with induction of model Hirano bodies (17,25). On the cellular level, this model system was used to demonstrate that Hirano body formation proceeds by formation of small aggregates, followed by consolidation into a single large Hirano body (26).…”
supporting
confidence: 61%
“…Therefore, it has been proposed that CTinduced model Hirano body formation may be the result of increased F-actin binding and loss of calcium regulation (16). Further studies using additional mutated forms of the 34-kDa protein are consistent with the conclusion that activation of actin binding and loss of calcium regulation are biochemical properties invariably associated with induction of model Hirano bodies (17,25). On the cellular level, this model system was used to demonstrate that Hirano body formation proceeds by formation of small aggregates, followed by consolidation into a single large Hirano body (26).…”
supporting
confidence: 61%
“…It is possible that the effects of Ca 2+ on cell mechanotype might be mediated through cytoskeletal actin, whose organization and dynamics are regulated by this divalent cation (Dushek et al, 2008;Young et al, 1994). The function and activity of actin-associated proteins that regulate crosslinking and severing also depend on Ca 2+ (Furukawa et al, 2003;Witke et al, 1993;Yamamoto et al, 1982). For example, the Ca 2+ -calmodulin complex binds to filamin, which is an actin crosslinker that regulates the cell mechanical phenotype (Kasza et al, 2009;Nakamura et al, 2005;Stossel et al, 2001).…”
Section: Discussion Cell Mechanotype and Invasive Potentialmentioning
confidence: 99%
“…These processes in turn influence cell shape, endocytosis, morphogenesis, locomotion, growth and division (Furukawa et al, 2003). For example, in Dictyostelium, Ca 2+ fluxes derived from extracellular Ca 2+ or intracellular Ca 2+ stores are required for cell spreading in locomotion and chemotaxis (Furukawa et al, 2003;Unterweger and Schlatterer, 1995).…”
Section: Role Of Ca 2+ In Flii-nmmiia Interactionsmentioning
confidence: 99%
“…These processes in turn influence cell shape, endocytosis, morphogenesis, locomotion, growth and division (Furukawa et al, 2003). For example, in Dictyostelium, Ca 2+ fluxes derived from extracellular Ca 2+ or intracellular Ca 2+ stores are required for cell spreading in locomotion and chemotaxis (Furukawa et al, 2003;Unterweger and Schlatterer, 1995). Consistent with these data and the notion that FliI is a Ca 2+ -dependent actin-capping protein, we found that when FliI WT cells were loaded with BAPTA-AM to clamp [Ca 2+ ] i , the association of FliI with NMMIIA, the formation of cell extensions and collagen compaction were all inhibited.…”
Section: Role Of Ca 2+ In Flii-nmmiia Interactionsmentioning
confidence: 99%